O34: WHO SHOULD BE FOLLOWING UP IN PATIENTS WITH PROSTATE CANCER USING PSAS?. (27th April 2021) - Lami, M; Jackson, G
Abstract: Introdution: Prostate cancer patients are usually followed up using serial PSA testing. NICE provides guidelines for PSA follow up however whether this should be in primary care or secondary care is ambiguous. Consequently, there is a concern that PSAs are being missed. The primary aim of this study was to understand whether PSAs were being missed. Method: A retrospective study was carried out at Whitehill General Practice. Patients were identified using codes for prostate cancer through Egton Medical Information Systems (EMIS) software. Data for patients followed up with PSAs between 2015-2019 was collected manually from documentation. Chi-squared statistical testing was used. Result: 47 patients had prostate cancer follow up with repeat PSAs. 45% patients were followed up solely by primary care whilst 40% had primary care follow up directed by specialists. 7 patients were excluded from further analysis. 35% of patients had missed PSAs, of which 18% had no reason documented. Furthermore, 19% had missed PSAs with solely primary care follow up. The difference in missed PSAs between solely primary care follow up versus those directed regularly by specialists was not significant (chi-squared 0.0177, p>0.05). Conclusion: PSAs are being missed because of a lack of a recall system. An 'out of hospital' recall system through a local administrative hub would allow for follow up standardisation. Involving patients in their follow up care should also be considered. By placing the responsibility centrally rather than to individual clinicians provides multiple fail safes to reduce missed follow ups. Take-home message: An 'out of hospital' recall system through a local administrative hub would allow for follow up standardisation. Involving patients in their follow up care needs to also be considered.